Using of aluminum (lignin /silica /fatty acids) hybrid filler in the fabrication of natural rubber conductive elastomers - Doaa S. Mahmoud; Khlood S. Abdel Zaher; Salwa H. El-Sabbagh; A. M. Yossef; Galal A.M. Nawwar (Scientific Reports)
Abstract Green flexible conductive composites (FCCs) with high flexibility and foldability have potential uses in wearables, artificial intelligence (AI), and other fields. This research explores the valorization of aluminum hybrid fillers (lignin, silica, and fatty acids) extracted from rice straw black liquor to develop sustainable rubber composites. The natural rubber (NR) matrix was reinforced with different fillers: sodium bentonite, silica, and a synthesized Al(LSF) hybrid filler. The blending was performed using a two-roll mill with certain working conditions. The characteristics of the Al(LSF) hybrid filler were analyzed in detail. The properties of mechanical, swelling, electrical conductivity and morphology of the synthesized rubber composites were assessed. Characterization revealed that Al(LSF) hybrid filler accelerates the vulcanization process of NR composites. Notably, the properties of the resulting composites, such as tensile strength, crosslink density, and reinforcement direction, are dependent on the filler grain size. Al(LSF) nanoparticles (< 40 nm) provide superior reinforcement due to their increased interfacial interaction with the NR matrix. Because of its better interaction and dispersion, the Al(LSF) hybrid filler exhibited more uniform distribution, according to SEM images. In contrast to sodium bentonite and silica, the Al(LSF)/NR composites exhibit improved electrical conductivity (σ) and dielectric permittivity (ε’). The addition of Al(LSF) to NR composites led to a pronounced increase in electrical conductivity (σ), reaching nearly 900% higher than that of the unfilled NR. The findings of this experiment are expected to facilitate the creation of economical and sustainable rubber composites for widespread use in rubber industries.